Client - side attacks and defense - Shimonski, Robert (Syngress, 2012)
Presents a framework for defending your network against attacks in an environment where it might seem impossible. This title discusses along with their delivery methods, such as browser exploitation, use of rich Internet applications, and file format vulnerabilities. It includes antivirus and anti-spyware, intrusion detection systems.